2020
DOI: 10.1007/s10886-020-01172-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and Electrophysiological Responses of Female Anopheles gambiae Mosquitoes to Volatiles from a Mango Bait

Abstract: Attractive Toxic Sugar Baits (ATSB) are used in a "lure-and-kill" approach for management of the malaria vector Anopheles gambiae, but the active chemicals were previously unknown. Here we collected volatiles from a mango, Mangifera indica, juice bait which is used in ATSBs in Tanzania and tested mosquito responses. In a Y-tube olfactometer, female mosquitoes were attracted to the mango volatiles collected 24-48 h, 48-72 h and 72-96 h after preparing the bait but volatiles collected at 96-120 h were no longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Alternatively, as dosing gradually increased to 10 g, females showed repellency. These dose-dependent reversal responses were reported by previous studies [56,57] as common responses, and it was confirmed in a recent study using plant volatiles that lower doses attracted while higher doses caused an avoidance response [58,59].…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, as dosing gradually increased to 10 g, females showed repellency. These dose-dependent reversal responses were reported by previous studies [56,57] as common responses, and it was confirmed in a recent study using plant volatiles that lower doses attracted while higher doses caused an avoidance response [58,59].…”
Section: Discussionsupporting
confidence: 84%
“…Our results also highlight the phenomenon that the most abundant components are not always responsible for the behaviour, which has been demonstrated also on Anopheles gambiae (Giles) [55]. The long-term stability of EOs-especially if they are exposed to direct sunlight or other environmental factors-is not sufficient for their direct application, as the ratio of behaviourally active components could alter quickly, resulting in the loss of behavioural effect [55]. Dispensers containing the key compounds in the optimal dose and composition would be a more reliable alternative for the application in pest management.…”
Section: Discussionsupporting
confidence: 73%
“…To fully understand the underlying reasons for the observed deterrent effect, we also have to consider the qualitative differences between the antennal active compounds in the three EOs. Our results also highlight the phenomenon that the most abundant components are not always responsible for the behaviour, which has been demonstrated also on Anopheles gambiae (Giles) [55]. The long-term stability of EOs-especially if they are exposed to direct sunlight or other environmental factors-is not sufficient for their direct application, as the ratio of behaviourally active components could alter quickly, resulting in the loss of behavioural effect [55].…”
Section: Discussionmentioning
confidence: 57%
“…For example, (E)‐3‐hexen‐1‐ol showed attractive effects on both genders of Phthorimaea operculella and female Anagrus nilaparvatae (Li et al., 2020; Mao et al., 2018); nonanal elicited a significant electrophysiological response and olfactory preference of Harmonia axyridis , meanwhile electroantennogram responses of male Hyphantria cunea also be detected when stimulated by nonanal (Tang et al., 2012; Xiu, et al., 2019b). In addition, Orseolia oryzivora showed electrophysiologically activity on (E)‐caryophyllene, and these compounds were also marginally attractive to female Anopheles gambiae (Meza et al., 2020; Ogah et al., 2017). In this article, we only tested olfactory preference of two mirid bugs species to the mixed attractant; thus, the spectrum of attraction still needs to be explored to make sure if it has a potential to control some other mirid bugs like Lygus pratensis or even some pests not belong to Miridae in the future research.…”
Section: Discussionmentioning
confidence: 99%